Tipologi Pemikiran tentang Kewenangan Sunnah di Era Modern - Maizuddin M. Nur (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2012)
The Islamic modern world, which was started since in the 19th century, provided various religious thoughts. One of them was thought on sunnah authority. This discourse attracted many scholars from various fields, which resulted to various perfectives on the discourse. Surely, the variety could be analyzed and categorized into certain types based on categorization of logic. The categorizing is viable because the various thought that were produced by modern- contemporer personages are not absolutely different from each other, where its form and character still can be divided. At least there are four typologies regarded to the thought on sunnah authority, they are: ideal totalistic, ideal restrictive, ideal generality and paradigmatic. These typologies are taken from various perfectives and supported by various approaches in understanding sunnah authority and hadith validation. These typologies also reflect modern personage‟s struggle in understanding sunnah authority and hadith validation in human life